2021
DOI: 10.1016/j.clnu.2021.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Gastrointestinal Dysfunction Score (GIDS) for critically ill patients – A prospective multicenter observational study (iSOFA study)

Abstract: Background & aims: To develop a five grade score (0e4 points) for the assessment of gastrointestinal (GI) dysfunction in adult critically ill patients. Methods: This prospective multicenter observational study enrolled consecutive adult patients admitted to 11 intensive care units in nine countries. At all sites, daily clinical data with emphasis on GI clinical symptoms were collected and intra-abdominal pressure measured. In five out of 11 sites, the biomarkers citrulline and intestinal fatty acid-binding pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 21 publications
3
69
0
7
Order By: Relevance
“…Recently, Bachmann et al found that there are few patients with 2 cardiovascular SOFA points, and the prognostic value of cardiovascular SOFA was poor in patients assessed for intra‐abdominal hypertension and gastrointestinal dysfunction 23‐25 . Our findings in a large sample of general ICU patients confirm this.…”
Section: Discussionsupporting
confidence: 82%
“…Recently, Bachmann et al found that there are few patients with 2 cardiovascular SOFA points, and the prognostic value of cardiovascular SOFA was poor in patients assessed for intra‐abdominal hypertension and gastrointestinal dysfunction 23‐25 . Our findings in a large sample of general ICU patients confirm this.…”
Section: Discussionsupporting
confidence: 82%
“…Monitoring and management of EFI and GI dysfunction is complicated due to the lack of robust and reproducible markers and multifaceted clinical presentation [ 49 ]. As no single straightforward marker reliably detects GI dysfunction, using composite scores combining several symptoms and signs could be helpful and should be considered [ 131 ]. EFI at the bedside is defined as features of GI dysfunction appearing during EN and consequently leading to reduction or discontinuation of EN.…”
Section: Question 10: How To Assess Gastrointestinal Intolerance?mentioning
confidence: 99%
“…In addition to TBSA, GI dysfunction was also associated with sepsis (Spearman’s r = 0.237, P < 0.001) (Table 6 , Additional file 2 : Table S2), but sepsis was not an independent risk factor for GI dysfunction in the multiple logistic regression analysis. The iSOFA study indicated that the Gastrointestinal Dysfunction Score (GIDS) combined with the SOFA score could better predict 28-day and 90-day mortality of critically ill patients than using a single SOFA score [ 42 ]. We found similar results, where the retrospectively scored GI dysfunction of our patients before or within 1 month after injury were strongly correlated with all-cause 90-day mortality, both in univariate and multivariate analyses ( P < 0.001, Additional file 2 : Table S3).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, repeated and massive GI haemorrhages further increase the risk of blood volume loss and even aspiration, which will cause secondary injury to severe burns and increase the risk of death. Recent GI dysfunction papers [ 42 , 45 ] have shown that GI bleeding is higher-level evidence of GI injury in critically ill patients, which strongly suggests GI failure.…”
Section: Discussionmentioning
confidence: 99%